The Routledge handbook of modern Turkish history
1 online resource (402 pages).
Keywords: This handbook is an innovative recasting and reinterpretation of modern Turkish history centered on war and society. It covers much neglected conflicts and wars and provides new insights about its complex politics, military, diplomacy, and people.The Turkish Republic was born after a series of wars which dismantled the Ottoman Empire and left the foundation of a state with new and reduced borders. Turkey's foreign policy has been characterized for the last century by Mustafa Kemal Atatrk's principle of "peace at home, peace in the world", but in practice, it has had to fight foreign wars outside of its geography and battle counterinsurgency inside its borders against various rebel movements. Although wars and conflicts were instrumental in shaping Turkey, they have received very little scholarly attention, and they are mostly absent in western studies of modern Turkey. Rather than advocating for a single accepted interpretation of Turkish history, this book aims to highlight the complexity of modern Turkish history and the diversity in interpretations.Presenting a coherent and condensed history of modern Turkey in a reader-friendly way, this handbook offers students and general readers the sound background to better understand Turkey within its international and transnational context.